Lymphedema: An early sign of rodent ulcer metastasis leads to timely intervention. Issue 8 (4th July 2019) - Mann, Caroline; Rietz, Stephan; Amedee, Ronald; Schepler, Hadrian
Abstract: Basal cell carcinoma has a potential for early and late metastasis. Depending on the location of the primary site, the relevant lymphatic drainage routes have to be monitored. Regional lymph edema may be a first indicator for metastasizing disease. Abstract : Basal cell carcinoma has a potential for early and late metastasis. Depending on the location of the primary site, the relevant lymphatic drainage routes have to be monitored. Regional lymph edema may be a first indicator for metastasizing disease.